The Relationship between Vocabulary Development and Motor Functions in Children With Cerebral Palsy - Aljadaan, Adel F. (Journal of Intellectual Disability - Diagnosis and Treatment, 2024)
Objectives: This study aimed to evaluate the relationship between vocabulary development and motor functions in children with Cerebral Palsy (CP). Methods: This study used questionnaires and survey methods. Sixty children with CP with different types and extremity distributions were included in the study. Data were analyzed using the SPSS 18.0 package program for frequency and percentage values related to demographic characteristics. The Spearman Correlation test was performed to determine the relationship between motor function levels and receptive language vocabulary development levels of children with CP. Results: Although there was no statistical significance between the receptive language vocabulary development level and motor function levels of children with CP, nine children with CP were at level 5, and sixteen were at level 4 on the GMFCS. According to MACS, ten children were at level 4, and nine were at level 3. Conclusion: In the evaluation of children with CP, gross motor development levels, manual skills, fine motor development monitoring, and language development levels can improve functional outcomes and participation in therapy programs.